2020
DOI: 10.1007/s12011-020-02496-y
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Trace Element Status (Zinc, Copper, Magnesium) and Clinical Outcomes in COVID-19 Infection During Pregnancy

Abstract: SARS CoV-2 is a novel coronavirus which has caused many deaths in the recent pandemic. This study aimed to determine zinc, copper and magnesium status on pregnant women with COVID-19. 100 healthy (33/32/35) and 100 SARS-CoV-2 positive (34/33/33) pregnant women were included in the study according to their trimesters. Blood samples were obtained from the patients along with the initial laboratory tests for clinical outcomes upon their first admission to hospital. In the first and third trimesters serum zinc lev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 30 publications
8
70
0
Order By: Relevance
“…Our finding is consistent with that of a prospective observational study conducted on COVID-19 inpatients at the time of hospitalization, which reported that the serum concentration of zinc was significantly lower in patients compared to healthy controls [48]. Additionally, a recent study in Turkey reported that in the first trimester of pregnancy, the serum concentration of zinc was significantly lower in pregnant women with COVID-19 compared to controls [49]. Moreover, a single-center study carried out on hospitalized patients with COVID-19 found that the serum concentration of zinc was significantly lower in patients who died than those who were admitted to an intensive care unit (ICU) or non-ICU and survived.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding is consistent with that of a prospective observational study conducted on COVID-19 inpatients at the time of hospitalization, which reported that the serum concentration of zinc was significantly lower in patients compared to healthy controls [48]. Additionally, a recent study in Turkey reported that in the first trimester of pregnancy, the serum concentration of zinc was significantly lower in pregnant women with COVID-19 compared to controls [49]. Moreover, a single-center study carried out on hospitalized patients with COVID-19 found that the serum concentration of zinc was significantly lower in patients who died than those who were admitted to an intensive care unit (ICU) or non-ICU and survived.…”
Section: Discussionsupporting
confidence: 92%
“…In humans, copper is involved in the structure of cytochrome C-oxidase and in oxidative stress-related steps, but high copper levels may have adverse effects during inflammation. The balance between zinc and copper is important for zinc to neutralize the adverse effects that copper can cause [24,41]. Therefore, we thought that the Zn/Cu ratio would be worth examining.…”
Section: Resultsmentioning
confidence: 99%
“…However, some people experience the disease in a mild asymptomatic phase, while others experience the disease in a severe symptomatic phase, which is another mystery of the disease that awaits scientific answers [20,21]. In our literature review, we found studies comparing urine [22] and serum trace element levels [21,23] and biochemical parameters (with another disease) [24] of COVID-19 patients with control groups. However, no study has been found showing how COVID-19 disease changes simultaneously with both biochemical parameters and serum trace element concentrations, according to the severity of the disease.…”
Section: Introductionmentioning
confidence: 95%
“…Pregnant women with COVID-19 have been reported to display a trimester-dependent increase in serum Cu concentrations, with small deviations only in comparison to healthy control pregnancies [34]. Interestingly, serum Cu was elevated in the pregnant women with COVID-19 specifically in the first and third trimester, but not in the middle of pregnancy [34]. Whether these dynamics constitute a positive and pregnancy-supporting response is unknown at present.…”
Section: Discussionmentioning
confidence: 99%
“…Whether supplemental Se will yield positive health effects in COVID-19 remains to be studied. The data base on Zn in COVID-19 is similarly limited, and low Zn concentrations are observed in severely diseased patients [33,34]. In contrast to the declining Se status in non-surviving patients, serum Zn levels seem to recover in COVID-19 during the hospital stay, indicative of a redistribution between circulation and immune cells [29].…”
Section: Introductionmentioning
confidence: 99%